Tren hijrah dan Isu Radikalisme Dalam Meningkatkan Kualitas Masyarakat Islam - Musa Musa (Sustainable, 2019)
The trend of appearance changes experienced by some Muslims in Indonesia is called the hijrah. The term hijrah itself actually has the meaning of moving. The move in question is the transfer of the Prophet Muhammad sallallaahu ‘alayhi wa sallam from Mecca to Medina because of the threat from the Quraysh tribe who opposed the Prophet's preaching calling for monotheism. But now the term hijrah is pinned to the movement of a person's change from being initially bad to getting better. For now, hijrah has a different form, which is identical to repent and look like using the robe, veil, for men to grow beards and so on. In this era, the trend of migration can easily be found in various circles of millennial. There are various factors that influence their hijrah actions, including being invited by friends, breaking up love, experiencing sad events, being aware of death and so on. This hijrah trend utilizes social media as a means of da'wah, friendship between Muslims and disseminating advisory posts. The issue of radicalism that arises which is pinned to those who emigrate is not true because emigration is an attempt by someone to get closer to the almighty Allah. Even if there is radicalism, it is the work of irresponsible people who act on behalf of certain parties. Abstrak Tren perubahan penampilan yang dialami oleh sebagian umat Islam di Indonesia disebut dengan hijrah. Istilah hijrah sendiri sebenarnya memiliki arti bergerak. Langkah yang dimaksud adalah pemindahan Nabi Muhammad sallallaahu ‘alayhi wa sallam dari Mekah ke Madinah karena ancaman dari suku Quraish yang menentang dakwah Nabi yang menyerukan monoteisme. Tapi sekarang istilah hijrah disematkan pada pergerakan perubahan seseorang dari semula buruk menjadi lebih baik. Untuk saat ini, hijrah memiliki bentuk yang berbeda, yang identik dengan bertobat dan terlihat seperti menggunakan jubah, kerudung, bagi pria untuk menumbuhkan janggut dan sebagainya. Di era ini, tren migrasi dapat dengan mudah ditemukan di berbagai kalangan milenial. Ada berbagai faktor yang memengaruhi tindakan hijrah mereka, termasuk diundang oleh teman-teman, putus cinta, mengalami peristiwa menyedihkan, menyadari kematian dan sebagainya. Tren hijrah ini memanfaatkan media sosial sebagai sarana dakwah, pertemanan antara Muslim dan penyebaran pos-pos penasehat. Masalah radikalisme yang muncul yang disematkan kepada mereka yang beremigrasi tidak benar karena emigrasi adalah upaya seseorang untuk mendekatkan diri kepada Allah SWT. Sekalipun ada radikalisme, itu adalah pekerjaan orang-orang yang tidak bertanggung jawab yang bertindak atas nama pihak-pihak tertentu.